Net Income and CSR Disclosure as Predictors Shares Price and Return per Share - Sari, Wahyuni Rusliyana; Matusin, Anita Roosmalina (JDM (Jurnal Dinamika Manajemen), 2019)
The purpose of this study was to determine the factors that influence shares price and return per share of 63 manufacturing companies period 2012-2016. The research method is multiple linear regression analysis, which done by the classical assumption test. The results of the research in the first model show that there is a positive influence between book value per share, net income, CSR social, and CSR report on shares price. While in the second model using the enter method shows delta net income and delta CSR total had a positive effect on return per shares, and delta CSR environment has a negative effect on return per share, while those using stepwise method delta CSR social and delta CSR net income had a positive impact on return per share. The contribution of this study is to provide information to stakeholders that CSR environment does not have an important role in shares prices, prioritizing the interests of shareholders, which means that the CSR environmental measurement instruments focus on disclosure, and ignore fundamental aspects, namely environmental liabilities. The implication is that the regulator, investor, and profession needs to more pay attention to CSR environmental.